EFEKTIVTAS LAYANAN TERPADU DALAM MENINGKATKAN PERCAYA DIRI PADA MATA PELAJARAN PPKN PADA ANAK TUNADAKSA - Ramani, Ramani; asni, Nur; Wahyuni, Delia; Andriani, Opi (Program Studi Pendidikan Vokasi Seni Kuliner, 2023)
This research focuses on children with special needs who are physically disabled (physically disabled) with the aim of increasing the students' self-confidence in participating in learning activities. The method used is qualitative descriptive. The analysis technique used was interviews and going directly into the field. The results of the research explained that students who experienced physical disabilities after birth were able to interact freely with their peers, had self-confidence when in class, and were active in learning activities. So students who have physical disabilities can also attend normal schools with the same facilities as normal children.